2021
DOI: 10.3389/fonc.2021.649035
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Lymph Node Metastasis and Its Prognostic Significance in Early Gastric Cancer: A Multicenter Study

Abstract: BackgroundEarly gastric cancer (EGC) is invasive gastric cancer that invades no deeper than the submucosa, regardless of lymph node metastasis (LNM). It is mainly treated by surgery. Recently, the resection range of EGC has been minimized, but cancer recurrence and overall survival in some patients should be given high status. LNM is an important indicator of prognosis and treatment in gastric cancer. The law of the number and location of metastatic lymph nodes in EGC is not yet clear. Therefore, we aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…[ 23 ] In addition, previous studies have demonstrated that macroscopic type and differentiation are independent risk factors affecting lymph node metastasis. [ 24 ] Tumor at body or lower third region has a tendency of more lymph node metastasis than that at the other locations, [ 25 ] consistent with our results.…”
Section: Discussionsupporting
confidence: 88%
“…[ 23 ] In addition, previous studies have demonstrated that macroscopic type and differentiation are independent risk factors affecting lymph node metastasis. [ 24 ] Tumor at body or lower third region has a tendency of more lymph node metastasis than that at the other locations, [ 25 ] consistent with our results.…”
Section: Discussionsupporting
confidence: 88%
“…Secondary brain metastasis from GOCs is relatively rare, occurring in 1.9% and 6% of patients with stage IV gastric and oesophageal adenocarcinomas, respectively [ 9 , 10 ]. Risk factors for developing metastasis include tumour depth of invasion at the primary site, invasion of the lymphatic or vascular system, an infiltrative growth pattern and poorly differentiated tumours [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to mention that age and tumor size were common risk factors. Tumor size has proven to be the independent risk factor for lymph node metastasis, significantly associated with the prognosis of patients with EGC [ 35 , 36 , 37 ]. Consequently, preoperative evaluation is crucial, and clinicians should comprehensively consider the relevant factors in choosing the appropriate treatment for patients with EGC.…”
Section: Discussionmentioning
confidence: 99%